2021
DOI: 10.3390/ph14090907
|View full text |Cite
|
Sign up to set email alerts
|

Benzydamine Reverses TMexCD-TOprJ-Mediated High-Level Tigecycline Resistance in Gram-Negative Bacteria

Abstract: Recently, a novel efflux pump gene cluster called tmexCD1-toprJ1 and its variants have been identified, which undermine the antibacterial activity of tigecycline, one of the last remaining options effective against multidrug-resistant (MDR) Gram-negative bacteria. Herein, we report the potent synergistic effect of the non-steroidal anti-inflammatory drug benzydamine in combination with tigecycline at sub-inhibitory concentrations against various temxCD-toprJ-positive Gram-negative pathogens. The combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Specifically, the activity of Tet(X) resistance enzyme was lower than 10% after treatment with 1,000 μg/mL Bi(NO 3 ) 3 . To further verify whether the synergy of Bi(NO 3 ) 3 is related only to tet (X)-mediated tigecycline resistance, we tested the synergistic activity between bismuth nitrate and tigecycline against tmexCD1-toprJ1 - or tet (A) variant-mediated tigecycline-resistant bacteria ( 24 , 25 ). However, no direct synergistic activity (FICI values of >0.5) was found in these strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the activity of Tet(X) resistance enzyme was lower than 10% after treatment with 1,000 μg/mL Bi(NO 3 ) 3 . To further verify whether the synergy of Bi(NO 3 ) 3 is related only to tet (X)-mediated tigecycline resistance, we tested the synergistic activity between bismuth nitrate and tigecycline against tmexCD1-toprJ1 - or tet (A) variant-mediated tigecycline-resistant bacteria ( 24 , 25 ). However, no direct synergistic activity (FICI values of >0.5) was found in these strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The synergism between antibiotics and bismuth compounds was measured using a 96-well flat-bottom plate according to previous studies ( 24 , 34 ). A total of 100 μL MHB was added to each well to construct an 8 by 8 system.…”
Section: Methodsmentioning
confidence: 99%
“…For example, azidothymidine, as an adjuvant of tigecycline, dramatically potentiates tigecycline activity against Tet(X)-mediated resistance of tigecycline to E.coli both in vitro and in vivo through inhibiting DNA synthesis and suppressing Tet(X) resistance enzyme activity (Liu et al, 2020). Recently, Tong et al showed that the non-steroidal antiinflammatory drug benzydamine in combination with tigecycline could reverse temxCD-toprJ-positive K. pneumoniae (Tong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the strategy is able to theoretically slow down the process of antibiotic resistance. Up to now, a few studies have been reported on non-antibiotic adjuvants of tigecycline ( Liu et al., 2020 ; Tong et al., 2021 ). For example, azidothymidine, as an adjuvant of tigecycline, dramatically potentiates tigecycline activity against Tet(X)-mediated resistance of tigecycline to E.coli both in vitro and in vivo through inhibiting DNA synthesis and suppressing Tet(X) resistance enzyme activity ( Liu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation